The Impact of Animated Video Material Interaction of Living Things with The Environment on Scientific Literacy of Junior High School Students - Ika Fitrianingsih; I Ketut Mahardika; Zainur Rasyid Ridlo (Journal of Science and Science Education, 2022)
This research aims to examine the impact of animated video on scientific literacy of junior high school students. Using a quasi-experimental research design with a non-equivalent control group design. The research was carried out at Wonomerto 1 state junior high school, with a population of class VII students in the even semester of the 2021/2022 academic year. The research sample consisted of the experiment class and the control class. Techniques and instruments of data collection using tests, observations, interviews, and documentation. The data analysis technique used a normality test, Independent T-test, and right-hand t-test. The results of the Independent Sample T-test of students’ scientific literacy abilities obtained a significance value (2-tailed) of 0.000 and the results of the right-hand t-test that the tcount > ttable value was 5,345 > 1,684. The results showed that learning science using animated videos had a significant effect on scientific literacy for junior high school students